Baricitinib in the treatment of rheumatoid arthritis: clinical and ultrasound evaluation of a real-life single-centre experience. (May 2021) - Tesei, Giulia; Cometi, Laura; Nacci, Francesca; Terenzi, Riccardo; Tofani, Lorenzo; Capassoni, Marco; Bartoli, Francesca; Fiori, Ginevra; Matucci-Cerinic, Marco; Bruni, Cosimo
Background: Ultrasound (US) is useful in monitoring RA patients, with the US7 score allowing grey-scale and power-Doppler (PD) semi-quantitative evaluation of synovitis and teno-synovitis. We evaluated real-life efficacy and safety of Baricitinib, an oral selective JAK1-2 inhibitor, in RA patients using clinical, clinimetric, and US assessments. Methods: Disease activity score in 28 joints calculated with C-reactive protein (DAS28-CRP), disease activity score in 28 joints calculated with erythrocyte sedimentation rate (DAS28-ESR), clinical disease activity index (CDAI), simplified disease activity index (SDAI), visual analogue scale (VAS)-pain, health assessment questionnaire (HAQ), COCHIN scale, adverse events (AE), concomitant medications, laboratory parameters, and US7 were performed/recorded at baseline, 1, 3, and 6 months in RA patients starting Baricitinib. Responder/non-responder status was determined according to the EULAR Response Criteria at 3 months. SDAI clinical remission or low disease activity (LDA) were calculated at 3 and 6 months. Results: In 43 enrolled patients, a significant improvement in disease activity and US7 components (except tendon PD) and a reduction of steroid dosage were observed. Responders at 3 months showed a significantly higher reduction of CDAI, SDAI, COCHIN scale, VAS-pain, and US7 synovialPD, compared with non-responders. At 3 and 6 months, remission/LDA was achieved by 12.8/53.8% and 21.6/51.3% patients, respectively. The csDMARD co-treatment was independently associated with remission/LDA at 3 months. Safety-related drop-outs were in line with literature data. The steroid dosage was associated with AE development at 6 months. Conclusion: The real-life data, also obtained with US evaluation, confirmed the Baricitinib efficacy in RA disease control, as well as the utility of assessment during the follow up of disease activity.